Values in Social Work and Professional Relationship Towards Users - Dragana Šćepović; Ljubo Lepir; Vesna Šućur-Janjetović (Društvene i Humanističke Studije, 2023)
The paper presents the results of comparative empirical research conducted among social work students (N=146), who were grouped into two subsamples: students from the Australian College of Applied Psychology, Sydney and Melbourne (N= 71), and students from Bosnia and Herzegovina (BiH) from the Universities of Banja Luka, Tuzla and Sarajevo (N=75). The subject of the research was the values in social work that determine the professional attitude and ways of intervening towards the users of the social protection system, among social work students in two different educational, cultural, and social-political environments (Australia and Bosnia and Herzegovina). The goal of the research was to determine whether there are differences in the attitudes and opinions of students about the values of social work, professional attitudes, and actions towards users of the social protection system, about the country of study and residence. The research was carried out using the research method (survey technique), for the needs of which a specially prepared instrument - Questionnaire (ORiSR/April 2020) was created, which examined students' attitudes about the professional relationship and measures of treatment towards users of social work services. The obtained results confirmed the assumed hypothesis that there are significant differences in students' attitudes regarding the place of study, that is, the different cultural and social circumstances in which future social workers are educated. Differences were observed in the evaluation of individual measures and forms of protection for users of social work services. Students from Bosnia and Herzegovina believe that adoption and foster care are preferable forms of protection for children without parental care, while the majority of students from Australia think that the adoption of children in same-sex unions should be allowed. Also, the obtained results showed that, even though the views of students from Australia and Bosnia and Herzegovina differ on some values of social work, essential differences were not observed in the values related to satisfying the primary interest of the user, subordinating personal principles to the values of social work and social activism of social work in the community.